Bird checklist and contributions to conservation of the Atlantic forest-cerrado ecotone in Três Lagoas municipality, Brazil - Sérgio Roberto Posso; Maurício Neves Godoi; Claudenice Faxina; Vagner de Araújo Gabriel; Lys Pereira de Souza; Fernando Igor de Godoy; Marcelo Alejandro Villegas-Vallejos; Luiz Arthur de Carvalho Cintra (Papéis Avulsos de Zoologia, 2023)
Abstract Although Três Lagoas municipality is located in a rare and highly fragmented Atlantic Forest-Cerrado ecotone, there is scarcity of biodiversity data to guide conservation decisions. Therefore, this study aimed to compile the first bird checklist in 31 localities in this municipality to propose conservation strategies based on avian richness, conservation and migratory status. A total of 419 bird species were recorded, of which 412 were exclusive to the Atlantic Forest-Cerrado ecotone and seven to the Cerrado domain (C. minor, L. xenopterus, P. unicinctus, T. curucui, S. pileata, S. melanopis and S. luteola). According to the results, 12 species are included in the Near Threatened category, four are vulnerable (C. fasciolata, L. xenopterus, A. tricolor and S. hypoxantha) and one is endangered (U. coronata). Regarding migratory birds, 112 were recorded (95 intracontinental, 17 intercontinental). Since the majority of these species are recorded in grasslands, aquatic habitats and Seasonal Deciduous Alluvial Forest, they necessarily have highest priority for conservation and restoration. Thus, we recommend that: (1) areas 2, 11 and 24 be considered as both Important Bird Area and “Area de Proteção Ambiental”; (2) riparian forest restoration along the Paraná river act as a local ecological corridor among these areas, allowing the recolonization, genetic exchange and restoration of locally reduced populations of migratory and near/threatened bird species.